Environmental justification for using of active yeast in laying hens diet - Orishchuk, O. S.; Orishchuk, O.; Orishchuk, Oksana; Оріщук, Оксана Сергіївна; Tsap, S.; Tsap, Svitlana; Tsap, S. V.; Tsap, Svitlana V.; Цап, Світлана Володимирівна; Chernenko, Oleksandr; Chernenko, O. M.; Chernenko, Oleksandr Mikolajovich; et al. (Alex Matsyura Press, 2019)
The results of the studying of active yeasts Saccharomy cescerevisiae influence on the egg-laying capacity and morphological characteristics of the hens "NOVOgen brown" breed eggs are presented. The nutritional intervention of active yeast Saccharomy cescerevisiae in laying hens diet allowed to increase egg-laying capacity by 3.7-6.6% and improve the morphological composition of the eggs. However, feed conversion in experimental groups was by 5.1-7.9% lower in relation to the control group. Наведено результати дослідження впливу активних дріжджів Saccharomy cescerevisiae на несучість та морфологічні показники яєць курок-несучок кросу “NOVOgen brown”. Введення у раціони курей-несучок активних дріжджів Saccharomy cescerevisiae дозволило підвищити несучість курок на 3,7–6,6 % та покращити морфологічний склад яєць. При цьому конверсія корму в дослідних групах була на 5,1–7,9 % меншою по відношенню до контрольної групи.
Екологічне обґрунтування використання активних дріжджів у годівлі курей-несучок
Оріщук Оксана Сергіївна https://orcid.org/0000-0002-6140-870х Цап Світлана Володимирівна https://orcid.org/0000-0002-2495-949х Черненко Олександр Миколайович https://orcid.org/0000-0002-8829-3148 Черненко Олена Іванівна https://orcid.org/0000-0002-5951-6576 Микитюк Віктор Васильович https://orcid.org/0000-0002-1346-4908
Keywords: productivity; продуктивність; hens; кури; combined feed; комбікорм; amino acid; амінокислотний склад; Saccharomy cescerevisiae; Saccharomy cescerevisiae